FIRST LANGUAGE IN FOREIGN LANGUAGE CLASSROOM DISCOURSE: IS IT NECESSARY? - Ribut Surjowati; Heru Siswahjudioko (PARADIGM: Journal of Language and Literary Studies, 2020)
To maintain the class alive, language choice used in the classroom plays an important role. So far, some English teachers have thought that they have to use English in the classroom during the learning process because it will encourage the learners to think and speak in English. In contrast, some research shows that the use of first language (L1) in the classroom will give positive benefits in the learners’ understanding to the subject learnt and responds during the discussion. This paper is intended to describe the positive effect and benefits of using L1 in the EFL classroom.